Employers’ priority on work skills and the skill gaps: a case of Thailand - Thunyalak Weerasombat; Pongsaya Pumipatyothin (Cogent Education)
This research analyzes how firms prioritize skill sets through exploring employers’ skill demand in Thailand. Referring to the eight skills identified in an earlier research, the data was collected through online questionnaires conducted from 310 HR managers/recruiters, which was analyzed through percentage, means, standard deviations, and One-Way ANOVA. Key findings reveal that skills are prioritized by firms in the following order: cognitive skills, social skills, EQ, thinking skills, growth mindset, information and digital literacy, communication and language skills, and creativity and innovative skills. The data also show a significant variation in skill demand across firm sizes (sig. = 0.009, particularly in terms of skill prioritization). We further explore skill gaps by comparing the employer’s skill demand with the supply of 350 Thai senior social-science students through their online self-evaluation surveys. It reveals the largest gap in thinking skills, followed by EQ, communication and language skills, information and digital literacy skills, creativity and innovative skills, growth mindset, cognitive skills, and social skills. The findings contribute valuable insights to the literature on work skills demanded by employers in a Southeast Asian country, which remains rare. Further, the findings hold practical implications, as a guideline for preparing and developing university students’ skills prior to entering the labor market.